Tooth loss and mortality risk: the mediating role of hs-CRP in a Chinese cohort - Wu, Donglei; Mao, Mingxin; Wang, Wei; Zheng, Henan; You, Hongxia; Chen, Weixuan; Xu, Ziyang; Zheng, Yuyan; Yuan, Li (Frontiers in Oral Health, 2025)
ObjectivesThis study aimed to evaluate the mediating effect of systemic condition on the relationship between tooth loss and mortality risk.Materials and methodsA 9-y follow-up prospective longitudinal study was conducted based on China Health and Retirement Longitudinal Study (CHARLS). The participants aged >45 y at baseline and were followed up from 2011 to 2020. Cox proportional hazards models were utilized to assess the relationship between tooth loss and both all-cause mortality with hazard ratios (HRs) and 95% confidence intervals (CIs) reported with adjusted possible confounders. Systemic inflammation markers, including high-sensitivity C-reactive protein (hs-CRP) and white blood cell count (WBCs), were collected from CHARLS blood sample data. A mediation analysis was conducted to determine the role of hs-CRP and WBCs in the relationship between tooth loss and mortality.ResultsA total of 13,201 participants met the inclusion criteria, of which 964 had tooth loss and 12,237 did not. During a median follow-up of 8.7 years, The multivariable-adjusted Cox regression models. The subgroup analysis indicated that the association was found to be stronger among older adults (≥80 years) (HR: 1.62, 95% CI: 1.09–2.41) and males (HR: 1.80, 95% CI: 1.34–2.40). Additionally, the mediation analysis result has showed that serum hs-CRP level rather WBC count mediated 3% of this effect.ConclusionsComplete tooth loss is associated with higher mortality in the Chinese population, with systemic inflammation (hs-CRP) as a mediator.